The impact of work life balance on employees job satisfaction in banking sector in Tanzania”. A case of TPB Bank Plc Dar es Salaam - Chitenje, Lilian G (Mzumbe University, 2026)
A dissertation submitted in partial fulfillment of the requirement for the award of a degree of Master’s of Business Administration (MBA-Corporate Management) of Mzumbe University